You Can’t B. cereus – A Review of Bacillus cereus Strains That Cause Anthrax-Like Disease - Baldwin, Victoria M. (Frontiers in Microbiology, 2020)
Emerging strains of Bacillus cereus, traditionally considered a self-limiting foodborne pathogen, have been associated with anthrax disease in mammals, including humans. The strains have emerged by divergent evolution and, as exchange of genetic material in the Bacillus genus occurs naturally, it is possible that further isolates will be identified in the future. The strains vary in their genotypes and phenotypes, combining traits of both B. cereus and B. anthracis species. Cases of anthrax disease associated with these strains result in similar symptoms and mortality rates as those caused by B. anthracis. The strains are susceptible to frontline antibiotics used in the treatment of anthrax and existing vaccines provide protection in animal models. The emergence of these strains has reignited the debate surrounding classification of the B. cereus sensu lato group and serves as a reminder that the field of medical microbiology is constantly changing and remains an important and ongoing area of research.